Phenology, thermal requirement, and ripening of the ‘BRS Isis’ grape grafted on different rootstocks in a subtropical condition - Sánchez, Camilo André Pereira Contreras [UNESP]; Tecchio, Marco Antonio [UNESP]; Callili, Daniel [UNESP]; de Souza, Reginaldo Teodoro; Smarsi, Ronny Clayton; Leonel, Sarita [UNESP] (FapUNIFESP (SciELO), 2024)
The replacement of traditional table grape cultivars with seedless genotypes has become common in Brazilian viticulture, especially in non-conventional regions under subtropical conditions. In the context of viticulture, it is crucial to highlight the pivotal role played by rootstocks, which exert a direct influence on phenological cycle, productivity, and grape quality. This study aimed to assess the duration of phenological stages, thermal demand, and maturation of the grape cultivar ‘BRS Isis’ grafted onto different rootstocks in a subtropical climate during three harvest seasons. The results indicated that the duration of phenological stages varied across harvest seasons, notably extending in the third harvest season due to adverse prevailing climatic conditions. Although no significant differences were observed in the rootstocks during the initial phases of the phenological cycle, they influenced the overall duration from pruning to harvest. Particularly noteworthy were the rootstocks ‘IAC 572’ and ‘1103P,’ that had earlier maturation in one of the assessed seasons. Consequently, a variation in thermal requirement was higher in the third harvest season. The analysis leads to the conclusion that climatic conditions have impacted the duration of phenological stages, thermal requirements, and the maturation of ‘BRS Isis’ grape bunches in subtropical regions.
Keywords: grafting; physicochemical characteristics; red grapes; vitiviniculture; white grapes